PENDAMPINGAN GURU SEKOLAH DASAR KABUPATEN BELITUNG DALAM MENGEMBANGKAN PEMBELAJARAN STEM (SCIENCE TECHNOLOGY ENGINEERING AND MATHEMATICS) MENGGUNAKAN IOT (INTERNET OF THINGS) - Jap Tji Beng; Fransisca Iriani Roesmala Dewi; Claudia Fiscarina; Desella Chandra; Felicita Mauli; Layla Adila Ramadhani; Sri Tiatri (Jurnal Bakti Masyarakat Indonesia, 2022)
The influence of technological development brought about a sophisticated concept called IoT or the Internet of Things. In order to keep up with the progress of industrial era 4.0, preparation is needed to improve student competence. Science, Technology, Engineering, and Mathematics (STEM) education can improve IoT-related competencies. Collaboration between the use of IoT and STEM learning is expected to help students prepare for the future. Therefore, research on STEM Learning through IoT has been conducted for the last two years. Based on the results of this research, this PKM (Community Service) aims to provide assistance to elementary school teachers in Belitung Regency in the introduction of STEM learning through the implementation of IoT media. The methods in implementing the community service are: (a) data collection through questionnaires, prior to the implementation of Teacher Mentoring, (b) implementation of Teacher Mentoring in the form of lectures on IoT, STEM, and the benefits of STEM learning through IoT, (c) discussions and reflections on the material, (d) QnA session, and (e) data collection after Teacher Mentoring session. Furthermore, the data from the questionnaire was processed using quantitative methods. 75 teachers were assigned to attend this PKM, however, only 72 questionnaire data was collected. The result of the PKM recorded through QnA and questionnaires filled out by the teacher is that this PKM was able to help teachers understand more about the meaning of STEM by IoT. The STEM learning model through IoT is considered by the teachers to be able to provide positive benefits for students. Teachers expect similar materials related to technological advances to be given to students in the future.ABSTRAK:Pengaruh perkembangan teknologi di dunia menghasilkan suatu konsep canggih dengan sebutan IoT atau Internet of Things. Untuk menghadapi kemajuan zaman di era industri 4.0 diperlukan persiapan untuk meningkatkan kompetensi siswa. Pendidikan STEM atau Science, Technology, Engineering, and Mathematics dapat menjadi wadah dalam meningkatkan kompetensi terkait IoT tersebut. Kolaborasi antara pemanfaatan IoT dengan pembelajaran  STEM diharapkan dapat mempersiapkan siswa menghadapi masa depan. Oleh sebab itu, penelitian mengenai Pembelajaran STEM melalui IoT telah dilaksanakan selama dua tahun terakhir. Berbasis hasil penelitian tersebut, PKM (Pengabdian Kepada Masyarakat) ini bertujuan untuk memberikan pendampingan guru Sekolah Dasar di Kabupaten Belitung dalam pengenalan pembelajaran STEM melalui implementasi media IoT. Metode dalam pelaksanaan PKM adalah: (a) pengumpulan data melalui kuesioner, sebelum pelaksanaan Pendampingan Guru, (b) pelaksanaan Pendampingan Guru berupa ceramah mengenai IoT, STEM, dan manfaat pembelajaran STEM melalui IoT, (c ) diskusi dan refleksi mengenai materi yang diperoleh, (d) tanya jawab, (e) pengumpulan data sesudah Pendampingan Guru. Selanjutnya data dari kuesioner diolah dengan menggunakan metode kuantitatif.  Guru yang ditugaskan hadir dalam PKM ini adalah 75 orang, namun data kuesioner yang terkumpul adalah 72.  Hasil dari PKM yang terekam melalui tanya jawab dan kuesioner yang diisi oleh guru antara lain, bahwa PKM ini telah dapat membuat para guru menjadi lebih paham arti STEM dengan IoT.  Model pembelajaran STEM melalui IoT ini dinilai guru dapat memberikan manfaat positif bagi pada siswa.  Para guru mengharapkan materi-materi sejenis yang terkait dengan kemajuan teknologi dapat diberikan di kemudian hari.